A joint moment projection method and maximum entropy approach for simulation of soot formation and oxidation in diesel engines. (15th January 2020) - Wu, Shaohua; Lao, Chung Ting; Akroyd, Jethro; Mosbach, Sebastian; Yang, Wenming; Kraft, Markus
Highlights: An efficient numerical approach for soot simulation in diesel engines is developed. This new approach is accurate, easy to implement and computationally cheap. It is based on an advanced method of moments to treat the detailed soot model. It enables a detailed analysis in soot formation in diesel engines at low CPU cost. Abstract: A joint moment projection method and maximum entropy approach for treating the soot population balance equations is developed and presented in this work. The moment projection method is used to solve the population balance equations and generate moments that are supplied to the maximum entropy approach as a post-processing technique to reconstruct the soot particle size distribution. The particle size range required by the maximum entropy for particle size distribution reconstruction is determined based on the weighted particles generated in the moment projection method. The performance of the joint approach is first evaluated by solving a set of simplified population balance equations in MatLab, then it is implemented into a Stochastic Reactor Model engine code to simulate the formation and oxidation of soot particles in a single-cylinder direct injection diesel engine. Results suggest that the joint approach has the advantages of ease of implementation, high accuracy and low computational cost. It enables a detailed analysis on the soot formation and oxidation processes in diesel engines. Complete information on the soot particle size distribution can be provided with little CPU cost induced.